Bordetella pertussis adenylate cyclase toxin: intoxication of host cells by bacterial invasion. - Mouallem, M (1990)
Bordetella pertussis produces extracytoplasmic adenylate cyclase toxin (AC toxin) which penetrates target cells and, upon activation by host calmodulin, generates high levels of intracellular cyclic AMP (cAMP). As a result, bactericidal functions of immune effector cells are impaired. Since a considerable amount of AC toxin is associated with the bacterium, it was proposed that the toxin may be delivered by direct interaction of the organism with the target cells (E. L. Hewlett, M. C. Gray, and R. D. Pearson, Clin. Res. 35:477A, 1987). Incubation of CHO cells with intact B. pertussis led to formation of intracellular cAMP at levels comparable to those produced in CHO cells by equivalent activities of isolated AC toxin. cAMP accumulation induced by the whole bacteria appeared after a lag of 40 to 60 min and reached high levels within 2 to 3 h, whereas adherence of the bacteria proceeded rapidly and reached a maximal level within 80 min. Sera of pertussis patients completely blocked cAMP accumulation induced by the whole bacteria without having a major effect on either bacterial adherence or cAMP production by the AC toxin. Cytochalasins B and D, inhibitors of bacterial invasion, abrogated the cAMP response to the whole bacteria but not the response to the AC toxin. These agents did not affect bacterial adherence. Transmission electron micrographs revealed that B. pertussis, within the time course of cAMP induction, invaded CHO cells. We suggest that cAMP induction by B. pertussis is caused by the entry of the whole bacteria into CHO cells rather than by delivery of AC toxin during bacterial adherence. This route of cell intoxication may be relevant to the pathogenesis of whooping cough.